Parameters of Stretto Use inside the Contrapunctus 5 of the Art of Fugue by Johann Sebastian Bach (BWV 1080, 5) - Alevizos, Konstantinos (Revue musicale OICRM, 2019)
In this article, my objective is to attempt to connect all the simultaneous compositional processes that J. S. Bach combined in order to create the stretto forms inside the Contrapunctus 5 of the Art of Fugue. The analysis offers a perspective by relating four technical elements present in every stretto of the subject; the distance of entry in each voice, the raw material used, the technique of inversion and the position of dux and comes.